PENGARUH PENAMBAHAN KELUWIH(Artocarpus camasi) TERHADAP MUTU FISIK, KADAR PROTEIN, DAN KADAR AIR ABON LELE DUMBO (Clarias gariepinus) - Rohmawati, Ninna; Sulistiyani, Sulistiyani; Ratnawati, Leersia Yusi (FKM - UNEJ, 2013)
One of the main nutritional problems in Indonesia is Protein Energy Malnutrition (PEM). Fish as protein source can be an alternative solution for PEM. Abon made from meat or fish have a high price.In order to make affordable price to the public,it is combined with plant-based ingredients (also known as abon modification). Objective of this research is to gain more understanding the influence of the addition of keluwih (Artocarpus camasi) against physical quality, protein content, and water content of the abon lele dumbo (Clarias gariepinus). Research experiment by using a quasi experimental design, there are 4 levels of treatment: P0 (abon lele dumbo without additional keluwih as control group), P1 (abon lele dumbo with additional keluwih 20 %), P2 (abon lele dumbo with additional keluwih 40 %), P3 (abon lele dumbo with additional keluwih 60 %) and 12 units experiment. Analysis of the first modifications done abon test power received (Hedonic Scale Test). Chemical analysis of protein levels with Semi Micro Kjeldahl Test and water content by using the way of heating (cawan method). The results of the analysis using the test results are significant, when Friedman then proceeded to test the Wilcoxon Signed Rank Test for knowing the difference of 4 degrees of treatment. Keluwih can be used in the manufacture of mixtures of abon lele dumbo (abon modification). There is a trend of decrease in the levels of protein with the increasing proportion of keluwih is added to the abon (ranges from 18.1% to 36.2%). There is a tendency of an increase in water content with the increasing proportion of keluwih is added to the modifications ranged from tivoid languages (6.7% to 12.1%). The right proportion of the addition of keluwih in making abon modifications is P1 (abon lele dumbo with additional keluwih 20 %). Keywords: keluwih, physical quality, protein content, water content, abon lele dumbo.